2018
DOI: 10.1515/labmed-2017-0144
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dynamic thiol/disulfide homeostasis in patients with asthma

Abstract: Background: Asthma is a chronic inflammatory lung disease and oxidative stress is an important component in airway inflammation. This study aims to investigate dynamic thiol/disulfide homeostasis in patients with asthma. Methods: A total of 103 subjects, including 56 patients with asthma and 47 healthy controls, of similar age and gender were included in the study. The native thiol, total thiol and disulfide levels and the disulfide-native thiol, disulfide-total thiol and native thiol-total thiol ratios were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This oxidation-reduction cycle between the thiol and DS groups ensures the maintenance of a dynamic thiol-disulfide balance, which is essential for several physiological processes, including, but not limited to, cell signaling, xenobiotics detoxification and antioxidant defense [10,11]. Recent studies have demonstrated that changes in the thioldisulfide balance are associated with the etiology and/or progression of various diseases [12][13][14][15]. This study aims to investigate the effects of smoking on dynamic thiol-disulfide balance in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…This oxidation-reduction cycle between the thiol and DS groups ensures the maintenance of a dynamic thiol-disulfide balance, which is essential for several physiological processes, including, but not limited to, cell signaling, xenobiotics detoxification and antioxidant defense [10,11]. Recent studies have demonstrated that changes in the thioldisulfide balance are associated with the etiology and/or progression of various diseases [12][13][14][15]. This study aims to investigate the effects of smoking on dynamic thiol-disulfide balance in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%